Analisis Yuridis Investasi Syariah Ditinjau Dari Peraturan Otoritas Jasa Keuangan Nomor 12/PJOK.04/2015 Tentang Penerapan Prinsip Syariah Di Pasar Modal - Anastasya Febriyani; Rani Apriani (Peneliti.net, 2022)
In Islamic regulation, speculation is mudharabah which means giving over various assets to an individual or business foundation for benefit. Nonetheless, not all current ventures run by Islamic regulation, which is the justification for why some speculation instruments utilize a sharia venture framework. Moreover, sharia speculation is interest in a business establishment with Islamic standards (Islamic regulation) directed by Islamic sharia. For a Muslim, doing everything as per strict guidelines is vital, one of which is as speculation. In view of the kind of exchange, speculation is separated into two, in particular Sharia venture and non-Sharia or customary venture. Sharia speculation is interest in a business establishment with the standards of Islamic regulation (Islamic regulation) directed by Islamic sharia. The utilization of sharia speculation depends on the Qur'an as the most noteworthy wellspring of regulation and Hadith. The study of fiqh is one of the sciences that talks about muamalah, specifically the connection between individuals connected with business. One of the distinctions among sharia and customary speculation is regarding the agreement.